THE EARTHENWARE CRAFT AT PEJATEN VILLAGE: ADAFTIBILTY TRADITION ART IN GLOBLIZATION ERA - Gede Artayani, Ida Ayu (International Conference on Cultural Studies, 2018)
This article criticizes aboutthe growing phenomenon in term of earthenware from Pejaten Village in the globalization era. The development of pottery handicraft faces the major challenges and compete with the modern products. Take on such this phenomenon, the artisans from Pejaten Village chose to be survive (in the effort to develop the tradition arts and be able to adjust (adaptif) for the market changes. The success determinants of traditional artisans in term of their adaptability with the development strategies in the form of the strength of cultural capital owned by the artisans itself, in the form of inheritance from generation by generation continuing make the pottery products, and maintain the collectivity with the other earthenware artisans. The determination of adaptability with Positive mindset, has a strong determination to develop as well as a good understanding of the changes through the process of learning and culture commodification, so that resulting the traditional ceramic product’s variety with an interesting design as a regional characteristic in the preservation of traditional culture.